Dampak AFTA terhadap Daya Saing Industri Petrokimia Olefin Indonesia - Sudirman, Iman; Djulius, Horas (Jurnal Trikonomika, 2010)
AFTA is an agreement among ASEAN countries that has begun to be implemented. Indonesia olefins petrochemical industry is also affected by the implementation of AFTA, which requires domestic and imported inputs. This study aims to describe the competitiveness of Indonesian products in the olefin industry and to estimate the impact of the CEPT-AFTA. The method used is descriptive analysis using Revealed Comparative Advantage (RCA) and Revealed Trade Advantage (RTA) for some sub-sectors olefin petrochemical industries from upstream to downstream. Export-import data used are secondary data from each country that analyzed in some point of time. The result of the calculation and description of existing data indicates that in general, the competitiveness of Indonesia petrochemical products in ASEAN are relatively low. Implementation of the CEPT-AFTA will further reduce the competitiveness of Indonesia petrochemical products.